Protective back-burning along the western boundary of Tharwa village in the pre-dawn hours of 18 January 2003 - Cutting, Jeff, 1945- (2003)
"Tennis Courts, Tharwa Village at 0235 hrs, 18:01:2003. With free burning fires to the south, west and north-west, and extreme fire weather predicted for the day ahead, at 2.30 am on the 18 January, the Captain of Southern Districts Bushfire Brigade at Tharwa, Val Jeffrey, fearing destruction of the village, commenced a two kilometre protective burn in shrubland along the western boundary"--Note from the photographer.
Title from caption list supplied by the photographer, see file NLA04/564.
Part of the collection: A blood red noon, photography of the Brindabella & southern ACT fires of January 2003.
Also available online
Purchased 2005.
Keywords: Prescribed burning -- Australian Capital Territory -- Tharwa -- Photographs; Fire engines -- Australian Capital Territory -- Tharwa -- Photographs; Wildfires -- Australian Capital Territory -- Photographs; Forest fires -- Australian Capital Territory -- Photographs; Natural disasters -- Australian Capital Territory -- Photographs; Tharwa (A.C.T.) -- Photographs